2008
DOI: 10.1093/geront/48.2.190
|View full text |Cite
|
Sign up to set email alerts
|

Actuation of Mobility Intentions Among the Young-Old: An Event-History Analysis

Abstract: The ability to identify potential "retirement migrants" may be of practical importance for state and local government officials as well as developers interested in recruiting or retaining young-old residents. Our study offers insight on the interpretation of stated mobility intentions. Moreover, consistent with early theoretical work in the field, our analysis suggests that empirical studies must account for heterogeneity among older movers in order to avoid misleading results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…Bradley and colleagues examined expectations and subsequent residential relocation of the young-old prospectively over a longer time period. Their study found that over an 8-year period, the relationship between stated expectations and actual moves lessened after the first 2 years (Bradley et al, 2008). Thus, it seems that older adults' expectations to move may indeed predict actual moves within the timeframe of a few years.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Bradley and colleagues examined expectations and subsequent residential relocation of the young-old prospectively over a longer time period. Their study found that over an 8-year period, the relationship between stated expectations and actual moves lessened after the first 2 years (Bradley et al, 2008). Thus, it seems that older adults' expectations to move may indeed predict actual moves within the timeframe of a few years.…”
mentioning
confidence: 96%
“…Research focused specifically on older adults' expectations to move has targeted samples at midlife (Robison & Moen, 2000;Schiamberg & McKinney, 2003), the young-old (Bradley, Longino, Stoller, & Haas, 2008), the old-old (Silverstein & Angelelli, 1998), rural or urban residents (Colsher & Wallace, 1990;Oh, 2003;Oldakowski & Roseman, 1986), parents (Silverstein & Angelelli, 1998), and retirees who had already moved once (Stoller & Longino, 2001). Results from these studies suggest that expectations are associated with stage of life, household composition, gender, social bonds, and residential satisfaction.…”
mentioning
confidence: 99%
“…By selecting this age group, which had not yet retired at the time of the survey, and focusing on their plans for the time immediately after retirement, we have been able to link the observations made to the specific age group in question more precisely than is usually possible in studies on migration and housing preferences of the retirees (seeSander et al 2010, p. 10f). 2 Studies in USA(Bradley et al 2008) and Denmark(Hansen and Gottschalk 2006, p. 38) indicate that plans of moving can indeed be seen to predict future moves.…”
mentioning
confidence: 99%
“…A seminal article by MacDonald and MacDonald (1964) provides a good definition of the network migration or NM process: "movement in which prospective migrants learn of opportunities, are provided with transportation, and have initial accommodation and employment arranged by means of primary social relationships with previous migrants" (p.82). Work by Longino, Perzynski, and Stoller (2002) and Bradley, Longino, Stoller, and Haas (2008) provides additional insight into the NM process for older adults. These scholars suggest pioneer migrants transmit information and offer support.…”
Section: Network Migrationmentioning
confidence: 99%